Implementasi Nilai-Nilai Demokratis dalam Pembelajaran Pendidikan Agama Islam di SMP - Nia Erviana; Marlina, Marlina; Muhamad Ikhsanudin (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Nurul Huda, 2024)
This study aims to analyze the implementation of democratic values in Islamic Education (PAI) learning at SMP Negeri 1 Buay Madang, which, despite being applied, still faces several challenges. This research is a descriptive qualitative study using interviews, observations, and documentation for data collection, along with Huberman's descriptive analysis technique. The findings indicate that democratic values are implemented through democratic-based learning methods such as discussion, question and answer, assignments, and cooperative learning, as well as teacher role models who foster positive habits in students. The democratic values that emerge include freedom of expression, tolerance, self-confidence, freedom to form groups, and teamwork. Supporting factors in the implementation of democratic values include adequate facilities, teacher creativity, and a school culture aligned with democratic values. However, there are also obstacles, especially on the part of students, such as individual differences, including learning motivation and limited time allocation for Islamic Education subjects.